2014
DOI: 10.1039/c4ra09474c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient preparation of ultralarge graphene oxide using a PEDOT:PSS/GO composite layer as hole transport layer in polymer-based optoelectronic devices

Abstract: We herein report an investigation of ultralarge graphene oxide (UL-GO) sheet/poly(3,4ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) thin composite layers fabricated by spin coating on an indium-tin-oxide (ITO) anode as hole transport layer (HTL) in polymer light-emitting diodes (PLEDs), as well as polymer solar cells (PSCs). Monolayer UL-GOs were first synthesized based on a novel solution-phase method involving pre-exfoliation of graphite flakes which were then mixed into the PEDOT:PSS solution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…10,11 In these organic devices, PEDOT:PSS is commonly used as a hole-transporting layer (HTL) because it has relatively high hole mobility for the alignment of the work function of interfacial layers between the electrode and active layer. 12 Because this decrease in the energy barrier at the electrode contacts improves device performance, applications using PEDOT:PSS as a hole-transporting material have been developed.…”
Section: 9mentioning
confidence: 99%
“…10,11 In these organic devices, PEDOT:PSS is commonly used as a hole-transporting layer (HTL) because it has relatively high hole mobility for the alignment of the work function of interfacial layers between the electrode and active layer. 12 Because this decrease in the energy barrier at the electrode contacts improves device performance, applications using PEDOT:PSS as a hole-transporting material have been developed.…”
Section: 9mentioning
confidence: 99%
“…Therefore, recently combination of GO and PEDOT:PSS have been reported to effectively work as an HTL in OPVs. It is reported that use of a thin layer of GO underneath PEDOT:PSS can effectively prevent corrosion of ITO and its further diffusion into the photoactive layer23. Lee, Da-Young et al 24,.…”
mentioning
confidence: 99%
“…As shown in Fig. 6, the bright and dark domains are observed in phase images, corresponding to PEDOT-rich grains and PSS-rich grains, respectively [23,27]. The shape of PEDOT-rich grains transforms from a short curved domain to a long stretched network with increasing the amount of UL-GO to 0.04 wt% [27].…”
Section: Resultsmentioning
confidence: 85%
“…The sensitivity changing behaviors may be attributed to the adsorption and desorption of methanol molecules of the sensing films. This improvement may be resulted in the separation of PEDOT and PSS chains, mainly because the coulombic attraction between PEDOT and PSS was weakened by oxygenated functional groups on UL-GO sheets [23,27]. These covalently bond between PEDOT chains and UL-GO sheets made the conductive network.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation